Perancangan Sistem Informasi Penelitian Pengabdian BIMA Internal LPPM UWHS - Rozaq Isnaini Nugraha; Arif Fitra Setyawan; Dwi Retnaningsih; Rohadi Jaka Raharja (Pusat Riset dan Inovasi Nasional, 2025)
SIPPMASBIMA UWHS stands for Sistem Informasi Internal Penelitian Pengabdian BIMA Internal UWHS (Internal Information System for Research and Community Service of UWHS), which is designed as a system architecture for uploading research and community service data. The urgency of this research lies in the fact that the previous system used for managing research and community service data at the UWHS LPPM had limitations in data uploading, and lecturers were not accustomed to the system used by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek). Therefore, the objective of this research is to develop a new system that is more integrated and user-friendly, with an interface and methods resembling the BIMA system of Kemendikbudristek, to support lecturers in adapting their data input practices in accordance with the ministry’s system. The method applied is Agile Development, ensuring flexibility in feature development based on user needs. The targeted outcomes include an information system, a journal publication (at least Sinta 4), and a system prototype.